The impact of sleep interventions on athletic performance: A systematic review - Cunha, L. A.; Costa, J. A.; Marques, E. A.; Brito, J.; Lastella, M.; Figueiredo, P. (Sports Medicine - Open, 2023)
Background Sleep is essential for maximal performance in the athletic population. Despite that, the sport context has many factors that can negatively influence athletes` sleep and subsequent recovery.